In-situ Capacitance Sensing for the Settlement of Magnetorheological Fluid: Simulation and Experiments - Zhang, Honghui; Zou, Zhiyuan; An, Na; Xiong, Ningsong; Yang, Xu (Frontiers in Materials, 2021)
In light of the insurmountable sedimentation of magnetorheological (MR) fluid, it is of great significance to ensure the performability of MR damper by introducing a sensing method for the MR fluid settling, and a key indicator to identify the health status of the MR damper is critical. However, the settling monitoring system for MR fluid nowadays can only function in laboratory with transparent and non-magnetic tubes, which is not qualified for the in-situ sensing in a steel-made cylinder. Under the analysis of an open plate capacitor (OPC) configuration, the relationship between the concentration of magnetorheological fluid and the capacitance is investigated by simulation and experiments, and based on OPC, an in-situ sensing method for settlement monitoring of magnetorheological fluid is designed. The long-time settling monitoring is carried out with home-made MR fluids, and the test results show that the sensing method can effectively reflect the status of settled MR fluids, and is potential to be utilized in the identification of MR fluid compression points, which provides the strategic signal for the probable active or operational re-dispersing of MR fluid.